POTENTIAL OF MODAL SHIFT FROM PRIVATE VEHICLES (CARS AND MOTORCYCLES) TO MRT AND TRANSJAKARTA (CASE STUDY: IMPLEMENTATION OF ELECTRONIC ROAD PRICING (ERP) IN JENDERAL SUDIRMAN STREET, DKI JAKARTA) - Shafira, Irna
Sudirman Corridor is the office corridor with the highest supply and demand in DKI Jakarta, with an occupancy rate of 75.4%. This corridor's thriving economic activities led to high mobility among the populace, mainly facilitated by private transportation. Consequently, this extensive reliance on private vehicles has resulted in persistent traffic congestion. To address this issue, the implementation of Transportation Demand Management (TDM) policies, specifically Electronic Road Pricing (ERP), is proposed as a potential solution to regulate private vehicle usage on this road. Simultaneously, the existence of Mass Rapid Transit (MRT) and TransJakarta facilities along Jenderal Sudirman Street is recognized as a crucial pull factor for encouraging public transportation adoption among travelers. The effectiveness of TDM policies depends on how travelers respond to them. Therefore, this research attempts to analyze the probability of mode shift from private cars and motorcycles to MRT and TransJakarta after the implementation of Electronic Road Pricing (ERP) on Jenderal Sudirman Street. Additionally, the study aims to examine the ideal ERP tariff to achieve a reduction in private vehicle usage on this street. Employing a multinomial logistic regression approach through stated preference analysis, this research explores that factors which influence mode shift preferences towards MRT and TransJakarta are travel cost, ERP tariff, gender, income, total owned cars, and total owned motorcycles. By implementing ERP, there is an 18.59% increase in the probability of choosing MRT and a 14.63% increase on TransJakarta. Moreover, a noteworthy reduction, amounting to 80.13% for motorcycles and 97.42% for cars, is also observed in the likelihood of choosing private vehicles, including motorcycles and cars, which travel along Jenderal Sudirman Street. This paper suggests the minimum ideal ERP tariff of Rp11,000 for motorcycles and Rp18,000 for cars for reducing private vehicle usage on Jenderal Sudirman Street.